Neonatal birth trauma: incidence and predisposing factors - Asril Aminullah; Novik Budiwardhana; Agus Firmansyah (Indonesian Pediatric Society Publishing House, 2016)
Background The incidence of birth trauma and its predisposing factors at a major teaching hospital in Indonesia had not been reported. Objective To find the incidence of birth trauma, calculate a risk assessment of predisposing factors, to study whether cesarean section lowers birth trauma, and to identify the variety of morbidity and mortality due to birth trauma. Methods The incidence was studied retrospectively from 4843 medical records from January 2000 through June 2001 using the ICD-10 classification. Birth trauma cases were then included in a case-control study for a risk assessment profile of predisposing factors with logistic regression analysis. Results Three hundreds and thirty five out of 4843 neonates were identified to have birth trauma. Analysis revealed that forceps extraction (OR=48.29; p<0.01), vacuum extraction (OR=25.37; p<0.01), breech vaginal delivery (OR=3.94; p=0.03), and cesarean section (OR=3.44; p<0.01) were significant risk factors. Macrosomic infant (OR=3.86; p=0.04) was also significant. Birth injury to face (ICD-10 code P15.4) was the most common finding, followed by cephalhematoma and bruising of the scalp. There was no mortality due to birth trauma. Conclusions The incidence of birth trauma was still high. Cesarean section was found to be one of the risk factors, but compared to forceps and vacuum extraction, the risk of trauma is considered to be more acceptable.